Treatment of ureteral stones using Holmium:YAG laser - (:unkn) unknown (Springer Netherlands, 2005)
Introduction: There has been a steady increase in the number of ureteroscopic laser lithotripsy. In addition to its soft tissue applications Holmium:YAG laser has also been found an excellent intracorporeal lithotripter for all kinds of stones. We here present the results of patients treated with Holmium: YAG laser lithotripsy in our clinic. Methods: Between June 1997 and December 2002, 205 patients with a diagnosis of ureteric calculi were treated with ureteroscopy using Holmium:YAG laser as an intracorporeal lithotriptor. The stones were localized in the distal ureter in 158 patients (77), middle and proximal ureter in 47 patients (23). Stones ranged in size from 5 × 5 mm to 20 × 10 mm and the operation time was about 35 minutes (ranged 25-65 minutes). Follow-up evaluations have done at first and third months. Results: The ureteral stone could not be reached in 10 patients (4.8). Stone fragmentation or removal was accomplished in all other patients. Four patients (1.9) had proximal migration of the fragments and later treated with extra corporeal shock wave lithotripsy, and three patients (1.5) had ureteral perforation. They were managed by double J stent placement. Two of the patients had ureteral obstruction on the third month of procedure. One of the patients was treated with open surgery. For the other one, ureteroscopic balloon dilatation was performed and catheterized by double J stent and there wasn't any complication after the removal of stent. Conclusions: Ureteroscopic Holmium:YAG laser lithotripsy is a safe, technically feasible and efficacious treatment for ureteral stones. © Springer 2005.
Keywords: Endoscopy; Holmium; Laser; Ureteral stones; Ureteroscopy